Performanc of Cooler Box Using TEC1-12715 On Various Cooling - Sormin, Ivan Alexander; Gunadnya, Ida Bagus Putu; Aviantara, I Gusti Ngurah Apriadi (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
A cooler box is a device used to store and keep ingredients cool and fresh. One of the efforts to develop a cooling source for made cooler boxes is to use a thermoelectric module TEC1-12715 that utilizes the Peltier effect. This study aims to determine the temperature reached in the cooler using TEC1- 12715 as a cooling device. The cooler box load without and with a cooling load (bottles filled with water with a volume of 600 ml each). The cooling load data and the coefficient of performance (COP) are displayed in a graph of observations every 6 minutes. All the analyzed data showed in the pictures and tables. The results showed that the cooler box temperature without load decreased by the increasing cooling time. The average temperature achieved was 17.08°C. The average water temperature in the cooler containing 2, 4, and 6 bottles of aqua was 21.56°C, 23.08°C, and 24.74°C, respectively. An increase in cooling load will increase the input power into the cooler box and lower the COP value of the cooling system